USING MEDICAL OBJECTS FOR CLINICAL RECORDS CLASSIFICATION - Anh, Hong Khoa; Minh, Nguyen Chau; Bao, Ho Quoc (Vietnam Journal of Science and Technology, 2012)
ABSTRACTIn this paper, medical objects are used as featuresto classify clinical records. Medical objects such as disease names, drug names, symptoms, examination indicators are extracted using an Unstructured Information Management Architecture (UIMA) based system. The extracted medical objects will be used against the  "bag-of-words" as the features of the clinical record in some classification algorithms. The results show that the precision of the classification results using medical objects is better in all algorithms, suggesting that medical objects contribute a significant part to the semantic of a clinical record.Keywords.information extraction, healthcare informatics